2009
DOI: 10.1159/000189197
|View full text |Cite
|
Sign up to set email alerts
|

Validation Study of the OHIO Chamber in Patients with Japanese Cedar Pollinosis

Abstract: Background: An artificial exposure chamber (OHIO Chamber), which allows dispersal of a fixed concentration of Japanese cedar (JC) pollen under stable conditions, was constructed. This study was conducted to identify the exposure conditions assuring validity of the clinical tests conducted using this chamber. Methods: Twenty-four adult patients with JC pollinosis were exposed to different concentrations of JC pollen: 0 (only during the summer period), 4,000, 8,000 and 12,000 grains/m3, and the nasal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…Results of this study demonstrated that the system was able to deliver an average pollen level of 982 pollens/m 3 (SD, 102 pollens/m 3 ), close to the pre‐study target of 1000 pollens/m 3 . The variation was within what is generally accepted in other EEC studies . The spatial distribution of pollens varied by 9%, similar to what has previously been found .…”
Section: Discussionsupporting
confidence: 90%
“…Results of this study demonstrated that the system was able to deliver an average pollen level of 982 pollens/m 3 (SD, 102 pollens/m 3 ), close to the pre‐study target of 1000 pollens/m 3 . The variation was within what is generally accepted in other EEC studies . The spatial distribution of pollens varied by 9%, similar to what has previously been found .…”
Section: Discussionsupporting
confidence: 90%
“…Environmental exposure chamber studies can offer the advantage of inducing allergic rhinoconjunctivitis after exposure to pollen in the context of a highly controlled environment. [1][2][3][4][5][6] This strategy might potentially mitigate uncontrolled confounding factors that are inherent in phase III therapy trials conducted in sensitive subjects during the natural allergy season (eg, variable exposure to pollen or a short in-season period). 6 However, there are 2 key knowledge gaps that need to be bridged before this goal can be achieved.…”
mentioning
confidence: 99%
“…This facility can accommodate up to 14 subjects in one setting. The concentration of JC pollen and the exposure time were set at 8000 grains/m 3 (measured every 3 min by laser particle counter) and 3 h, respectively, according to the findings of a previous validation study23.…”
Section: Methodsmentioning
confidence: 99%
“…This rating system has been validated in the previous study23 and is different from that used in clinical trials in Europe and the US.…”
Section: Methodsmentioning
confidence: 99%